Toward Precision Psychiatry in Bipolar Disorder: Staging 2.0 - Salagre, Estela; Dodd, Seetal; Aedo, Alberto; Rosa, Adriane; Amoretti, Silvia; Pinzon, Justo; Reinares, Maria; Berk, Michael; Kapczinski, Flavio Pereira; Vieta, Eduard; Grande, Iria (Frontiers in Psychiatry, 2018)
Personalized treatment is defined as choosing the ‘right treatment for the right person at the right time’. Although psychiatry has not yet reached this level of precision, we are on the way thanks to recent technological developments that may aid to detect plausible molecular and genetic markers. At the moment there are some models that are contributing to precision psychiatry through the concept of staging. While staging was initially presented as a way to categorize patients according to clinical presentation, course and illness severity, current staging models integrate multiple levels of information that can help to define each patient’s characteristics, severity and prognosis in a more precise and individualized way. Moreover, staging might serve as the foundation to create a clinical decision-making algorithm on the basis of the patient’s stage. In this review we will summarize the evolution of the bipolar disorder staging model in relation to the new discoveries on the neurobiology of bipolar disorder. Furthermore, we will discuss how the latest and future progress in psychiatry might transform current staging models into precision staging models.